Analysis Of Mathematic Representation Ability In Online Learning - Erita, Selvia; Mulyani, Tami; Putra, Aan (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
ABSTRACT The outbreak of the corona virus has had an impact on various sectors, especially the education sector. The application of online learning has been implemented in almost all schools in Indonesia. However, judging from the results of various studies and some experiences, the online learning process in Indonesia has previously been carried out well. Mathematical representation skills are needed so that students understand mathematical concepts well. This study aims to analyze the ability of mathematical representation in online learning. The method used is descriptive qualitative type. The instrument used is a mathematical representation ability test and interview guidelines. The data analysis technique used is the stages of data reduction, data display and making overall conclusions. Data analysis of test results was used to determine the level of students' mathematical representation abilities, while interviews were to strengthen test results and determine student learning constraints. Based on the results of the study, it was found that students' visual representations were more dominant than other types of representations. The students' mathematical visual representation ability is in the sufficient (moderate) category, while the students' symbolic representation ability is very poor and the students' verbal representation ability is in the poor category.